Temporal Temperature Variation in Urban Gardens Is Mediated by Local and Landscape Land Cover and Is Linked to Environmental Justice - Nolte, Alejandro Castillo; Buchholz, Sascha; Pernat, Nadja; Egerer, Monika (Frontiers in Sustainable Food Systems, 2022)
As cities densify and sprawl, the urban heat island (UHI) effect remains a major threat to society. Due to morphology and material properties, cities tend to absorb and hold more heat than rural areas, resulting in higher temperatures inside urban areas. In response, urban greening through various local to landscape management is a proposed strategy to combat UHI. For example, urban community gardens are multifunctional urban greeneries in cities. Urban gardens have played an important role as meeting places for community members and hence, an important element of the social capital. But the role of urban gardens in urban cooling and combating UHI remain unclear, and specifically also how temperatures fluctuate daily within gardens in relation to garden management factors and city landscape context. In this study, we investigated temperature parameters of urban gardens interesting from an urban microclimate and UHI perspective, including diurnal and nocturnal temperature ranges, daily maximum temperature, and daily minimum temperatures in 18 gardens over the peak of the summer growing season of 2020. We then analyzed how these temperature parameters were correlated to surrounding impervious land cover in the landscape at various spatial scales (500m, 1000m and 2000m) and to local land cover factors within the garden (e.g., rock, bare soil, grass). We found that nocturnal temperature range is strongly negatively correlated to imperviousness at the landscape scale, and that the relationship decreases in strength with increasing spatial scale. This result is in line with previous research supporting the importance of evapotranspiration processes of surrounding green areas for nocturnal cooling of urban areas. In addition, some local land cover factors also were important for temperatures, indicating heating or cooling management mechanisms from within urban gardens. The results of this work can have important implications for resource use in urban agriculture, crop selection in urban agriculture, and ultimately growing food in urban environments.